2019
DOI: 10.1002/ppul.24320
|View full text |Cite
|
Sign up to set email alerts
|

Asthma control in children: Body plethysmography in addition to spirometry

Abstract: Background There is a lack of agreement among measures of asthma control in children. In Central Europe, body plethysmography is additionally used for asthma monitoring. However, its value is still unclear. Objectives We investigated the possible additional value of body plethysmographic measures (specific resistance, residual volume‐total lung capacity ratio [RV/TLC]) compared with spirometric measures forced expiratory volume in 1 second (FEV 1), forced vital capacity (FVC), FEV 1/FVC, forced expiratory flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
0
3
0
2
Order By: Relevance
“…There are differing opinions on the utility of body plethysmography to monitor asthma control. Korten et al performed a cross‐sectional study to analyze whether or not there was an association between body plethysmography values and asthma control as assessed by either a physician's history or questionnaire 12 . They found that the combination of spirometry with body plethysmography had greater agreement of asthma control compared to either alone.…”
Section: Monitoring Testsmentioning
confidence: 99%
“…There are differing opinions on the utility of body plethysmography to monitor asthma control. Korten et al performed a cross‐sectional study to analyze whether or not there was an association between body plethysmography values and asthma control as assessed by either a physician's history or questionnaire 12 . They found that the combination of spirometry with body plethysmography had greater agreement of asthma control compared to either alone.…”
Section: Monitoring Testsmentioning
confidence: 99%
“…При исследовании ФВД ОФВ 1 был снижен только у 6 (14,3%) пациентов. По данным других исследователей, показатели ФВД у детей с БА часто бывают в пределах возрастной нормы, особенно при легком или контролируемом течении [11,12].…”
Section: результаты и обсуждениеunclassified
“…Todėl gali padėti atskirti sutrikusį pasipriešinimą bei pralaidumą smulkiuosiuose kvėpavimo takuose. Taigi, remiantis atliktų tyrimų ir mūsų tyrimo duomenimis, sRaw vertingas diagnozuojant obstrukcines plaučių ligas [14][15][16][17].…”
Section: Moksliniai Darbai Ir Apžvalgosunclassified